Comprehensive Physiotherapy Program Improves the Medial Longitudinal Arch of a Male Adolescent with Bilateral Flexible Flat Foot: A Case Report - Sayu Aryantari Putri Thanaya; Chika Nabella Jamaluddin (Universitas Udayana dan Diaspora Taipei Medical University, 2021)
Introduction: Flat foot is a common foot deformity marked by the absence of the medial longitudinal arch of the foot. Flexible flat foot is usually symptomless but can affect the biomechanics of the lower extremity and lumbar spine, possibly increasing the risk of pain and injury. Conservative management, including physiotherapy, is important in flat foot management, yet the number of reports regarding physiotherapy for flat foot is scarce. Therefore, this case report aimed to describe a case of bilateral flexible flat foot in a male adolescent who was treated with a comprehensive physiotherapy program. Case Description: A 17-year-old male presented to the physiotherapy clinic with flat foot deformity on both feet. The patient received an hour of comprehensive physiotherapy program per session, twice per week, which included lower extremity stretching, various foot and leg strengthening exercises, proprioception exercises, and an educational aspect. The footprint test was conducted and the patient was evaluated using the Arch Index. The Arch Index measurements according to Cavanagh and Rodgers decreased from 0.38 to 0.32 (left foot) and 0.35 to 0.28 (right foot). Likewise, Staheli’s Arch Index measurements also decreased from 1.54 to 1.02 (left foot) and 1.5 to 0.7 (right foot). Conclusion: Following 20 physiotherapy sessions, the patient’s Arch Index measurements demonstrated an overall reduction, indicating noteworthy improvements in the medial longitudinal arch height. Hence, it can be concluded that a comprehensive physiotherapy program can help improve the medial longitudinal arch height, and thereby foot posture, of an adolescent with bilateral flexible flat foot.